Teacher’s strategies for managing talkative students at ELSI Padang - Alif, Rizkan; Fatimah, Sitti (Journal of English Language Teaching, 2025)
This study explores the strategies employed by ELSI teachers in managing talkative students within an English-only classroom environment. Talkative students can bring positive energy and active participation into classroom interaction, yet excessive talkativeness may disrupt lessons and limit quieter students’ chances to speak. This research aimed to reveal how teachers transform such behaviour into meaningful learning opportunities that promote motivation and engagement. A qualitative case study design under a post-positivist paradigm was applied, involving classroom observations and interviews with an experienced teacher at ELSI Padang. The data were analysed thematically using Self-Determination Theory (SDT) as the analytical framework to understand how teachers fulfil students’ psychological needs for autonomy, competence, and relatedness. The findings revealed six major strategies: balancing participation, motivating students through recognition and competition, fostering a supportive and enjoyable English-only environment, adapting teaching methods to learner diversity, maximizing peer influence, and maintaining positive perceptions toward talkative students. These strategies allowed the teacher to transform talkative behaviour into a motivational asset that enhanced students’ participation and confidence in speaking English. The study provides valuable insights for teachers and practitioners in non-formal English education contexts on managing active classroom dynamics effectively.